PERSEPSI PETANI RAKYAT TERHADAP PERAN PENYULUHAN PERKEBUNAN DI DESA SUNDATA KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN - Nadia Martin Nella; Cepriadi Cepriadi; Evy Maharani (DINAMIKA PERTANIAN, 2017)
Economic development in the agricultural sector has a very important role in the economy of developing countries, especially Indonesia which contributed most to the national development. It is understood that the welfare of farmers and rural communities will increase, which will ultimately improve the standard of living in most people and would enhance the overall national income. The purpose of this study was to determine the counseling implementation cocoa plantations in the village of Lubuk Sikaping Sundata District of Pasaman District, as well as to analyze the perception of the role of smallholder farmers in the village extension Sundata District of Lubuk Sikaping Pasaman district. This research was conducted in the District of Lubuk Sikaping Kanagarian Sundata, Pasaman District, with the consideration that Kanagarian Sundata needs counseling role for cocoa communities using survey methods. In this study, the sampling technique used (Proportionate Random Sampling), the sampling of members of the population at random and proportional. The population of farmer groups of 138 people, so by using the formula Slovin obtained as many as 57 respondents. The results showed that the implementation of the extension in Kanagarian Sundata can generally be said to be doing well because of compliance with elements of counseling. Farmer's perception of the role of agricultural extension officers in their duties categorized as "instrumental" well. Recapitulation of farmers' perceptions of the role of educator average number of seven factors: 2.53 with the category of "acts". The lowest score by category "no role" that is the perception of the role of educator as education and dissemination of information/innovation, while the perception of the role of educator as a facilitator, consultant, coaching, monitoring, and evaluation has the highest score by category "topic" well.